CANGKEMAN SEBAGAI SUMBER IDE DALAM KARYA SENI LUKIS - Pratama, Kurnia Aji; Purwantoro, Agus (TEXTURE Art and Culture Journal, 2024)
This article reveals the idea of painting using acrylic paint on canvas, which is inspired by the increasingly worrying conditions in the surrounding environment. The problem discussed is regarding the description of cangkeman, cangkeman is one of the expressions to convey opinions, feelings, and circumstances at that time. So far, many parties do not know how to express their feelings. Cangkeman has many roles in people's lives, namely positive roles and negative roles. This painting has a texture that is created spontaneously with acrylic paint strokes using a brush and palette knife. Cangkeman provides an overview of the expression of a person's heart so that in this final project cangkeman becomes the source of ideas for creating paintings because it has meaning, meaning of life.